Study on the correlation of nutritional status with clinical and pathological characteristics of patients with IgA nephropathy - Du Yan-bin; Du Yan-ling; Li Huan; Yuan Zu-jun (Linchuang shenzangbing zazhi)
ObjectiveTo explore the correlation of serum total protein， albumin， and prognostic nutritional index （PNI） with the clinical and pathological characteristics of IgA nephropathy （IgAN）， and to evaluate the impact of these nutritional indicators on the severity of IgAN.MethodsA total of 218 IgAN patients who were treated at Nephrology Department of Nanchong Central Hospital from January 1， 2019， to April 1， 2024 were included in this study. Baseline data， blood biochemistry results， nutritional and renal function indicators were collected from the patients. Pathological evaluations were performed according to the Oxford classification based on the results of percutaneous renal biopsy. Patients were divided into high/low nutritional status groups based on the median of PNI， and serum total protein， and albumin levels， and the clinical and pathological characteristics of different groups were compared.ResultsIn the high and low total protein groups， high and low albumin groups， and high and low PNI groups， significant changes in renal function-related indicators were observed as nutritional levels increased. Compared to the low total protein group， the high total protein group had significantly lower serum creatinine［（112.41 ± 21.86）μmol/L vs （93.54 ± 20.44）μmol/L］， and cystatin C ［1.14（0.81，1.22）mg/L vs 0.92（0.77，1.16）mg/L］ （P<0.05）， and a higher estimated glomerular filtration rate （eGFR） ［85.26（74.34，98.78）mL·min-1·（1.73 m2）-1 vs 111.34（92.56，118.92）mL·min-1·（1.73 m2）-1］ （P = 0.005）. Compared to the low PNI group， the high PNI group had lower serum creatinine［（111.33 ± 17.66）μmol/L vs （88.42 ± 15.34）μmol/L］， cystatin C［1.13（0.88，1.24）mg/L vs 0.86（0.61，0.99）mg/L］ （P<0.05）， and a higher eGFR［64.27（49.37，88.53）mL·min-1·（1.73 m2）-1 vs 104.35（89.25，128.81）mL·min-1·（1.73 m2）-1］ （P = 0.001）. Moreover， in all groups， higher nutritional levels corresponded to better prognosis of IgAN pathological types， indicating less severe renal injury （P<0.05）. Logistic regression analysis showed that only PNI had a significant statistical impact on whether IgAN patients had severe mesangial proliferation of glomerular capillaries. A higher PNI was associated with less severe mesangial proliferation （OR = 0.559， 95% CI： 0.339-0.932， P = 0.016）.ConclusionSerum albumin， total protein， PNI， and other nutritional indicators are correlated with the clinical and pathological characteristics of IgAN patients. PNI can be used as an auxiliary indicator to assess the severity of pathology， pathological classification， and corresponding treatment decisions， thus improving treatment outcomes and prognosis in IgAN patients.